A comprehensive study on vibration characteristics of corrugated cylindrical shells with arbitrary boundary conditions. (15th October 2022) - Liu, Yunfei; Zhu, Runze; Qin, Zhaoye; Chu, Fulei
Highlights: Vibration characteristics of corrugated cylindrical shells with arbitrary boundary conditions are studied. An equivalent orthotropic shell model for corrugated structures is developed. Analytical model for corrugated structures is verified by FE simulations and experimental study. The influences of key parameters on dynamic responses of corrugated shells are discussed. Abstract: The vibration characteristics of corrugated shells under arbitrary boundary conditions are investigated by theoretical analysis, finite element simulation and experimental verification. Firstly, based on a homogenization analytical technique, the equivalent orthotropic shell model is set up. Then, the strain-displacement relationships are received by Love thin shell theory, where artificial springs are applied to denote the arbitrary boundary conditions. Afterwards, modified Fourier series are selected to represent the displacement fields, and the Rayleigh-Ritz method is employed to acquire natural frequencies of corrugated shells. The modal expansion approach is applied to gain forced vibration responses. Finally, the effects of unit cell half period, unit cell radius, unit cell height and different boundary conditions on vibration characteristics of corrugated shells are studied.